2021
DOI: 10.7717/peerj.10741
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and functional analysis of the Hydroxycinnamoyl-CoA: shikimate hydroxycinnamoyl transferase (HCT) gene family in poplar

Abstract: Hydroxycinnamoyl-CoA: shikimate hydroxycinnamoyl transferase (HCT) divides the mass flux to H, G and S units in monolignol biosynthesis and affects lignin content. Ten HCT homologs were identified in the Populus trichocarpa (Torr. & Gray) genome. Both genome duplication and tandem duplication resulted in the expansion of HCT orthologs in Populus. Comprehensive analysis including motif analysis, phylogenetic analysis, expression profiles and co-expression analysis revealed the divergence and putative functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Dirigent protein not only plays an important role in the synthesis of plant secondary metabolites, but also participates in the plant stress resistance in Arabidopsis thaliana (Modolo et al, 2020). Hydroxycinnamoyl transferase (HCT) divides the mass flux to H, G and S units in monolignol biosynthesis and affects lignin content in Populus (Chao et al, 2021). In addition to A .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dirigent protein not only plays an important role in the synthesis of plant secondary metabolites, but also participates in the plant stress resistance in Arabidopsis thaliana (Modolo et al, 2020). Hydroxycinnamoyl transferase (HCT) divides the mass flux to H, G and S units in monolignol biosynthesis and affects lignin content in Populus (Chao et al, 2021). In addition to A .…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxycinnamoyl transferase (HCT) divides the mass flux to H, G and S units in monolignol biosynthesis and affects lignin content in Populus (Chao et al, 2021). In addition to A. lappa, other plants of the Asteraceae are also enriched in these genes.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis showed that the PAL genes were clustering with the reported PAL from monocotyledonous cereal crops, like rice and triticum, rather than the PAL from dicotyledonous plants such as Arabidopsis ( Zhu et al., 1995 ; Liao et al., 1996 ) ( Figure 3D ). Si016926m clustering with the HCT/HQT genes that had been reported to transfer hydroxycinnamate to shikimate or quinine, and is involved in the formation of phenolic acid ( Chao et al., 2021 ) ( Figure 3E ).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, p -hydroxyphenyl (H), guaiacyl (G), and syringyl (S) lignin were the only known lignin monomers. Recent studies have reported that catechyl (C) and 5 - Hydroxy -guaiacyl (5H) monomers contribute to lignin polymerization in some plant species [ 17 , 18 , 19 , 20 ]. A total of 11 lignin family enzymes and 24 metabolites are currently associated with the lignin pathway [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%